2011
DOI: 10.1063/1.3586812
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between relaxation pathways by combining dissociative ionization pump probe spectroscopy and ab initio calculations: A case study of cytosine

Abstract: We present a general method for tracking molecular relaxation along different pathways from an excited state down to the ground state. We follow the excited state dynamics of cytosine pumped near the S(0)-S(1) resonance using ultrafast laser pulses in the deep ultraviolet and probed with strong field near infrared pulses which ionize and dissociate the molecules. The fragment ions are detected via time of flight mass spectroscopy as a function of pump probe delay and probe pulse intensity. Our measurements rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 39 publications
3
63
0
Order By: Relevance
“…Figure 3 of archetypal geometries where two or three states are found to be (near) degenerate (energy difference smaller than 0.1 eV). Among the geometries where the S 0 and S 1 states are close in energy, two geometries similar to the twist and sofa S 0 /S 1 conical intersections reported by Kotur et al 48 could be identified. Figure 3a shows our twist structure, with the carbon atoms twisted by about 70°around the CC double bond.…”
mentioning
confidence: 80%
“…Figure 3 of archetypal geometries where two or three states are found to be (near) degenerate (energy difference smaller than 0.1 eV). Among the geometries where the S 0 and S 1 states are close in energy, two geometries similar to the twist and sofa S 0 /S 1 conical intersections reported by Kotur et al 48 could be identified. Figure 3a shows our twist structure, with the carbon atoms twisted by about 70°around the CC double bond.…”
mentioning
confidence: 80%
“…36 and to the analogues optimized for cytosine at different levels of theory. [21][22][23][24][25][26][30][31][32] Its relative energy is 31 375 cm −1 . It is characterized by a twisted C 5 -C 6 bond, with a bond length of 1.468 Å and a H-C 5 -C 6 -H dihedral angle of 122…”
Section: Radiationless Decay Mechanismsmentioning
confidence: 99%
“…9 The interest in the photophysics of Cyt has motivated many theoretical studies, whose main aims were to explain the ultrashort excited-state lifetimes and the formation of the long-lived triplet state. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Most studies have considered the amino-keto tautomer. Among the points of debate is whether the structure of the S 1 minimum of (ππ * ) character, 1 (ππ)* Min , has a quasi-planar or ring-puckered conformation, for a recent discussion see Ref.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation
“…The peak intensities of the pulses were about 0:3 TW=cm 2 for the UV (low enough to avoid saturating the S 0 -S 2 transition or producing any ion signal) and about 10 TW=cm 2 for the IR. The experimental setup is described in more detail in [22].…”
Section: Experimental Apparatusmentioning
confidence: 99%